Effect of dust cleaning on the enhancement of the power generation of a coastal PV-power plant at Zahrani Lebanon. (15th May 2019) - Hammoud, Mohammad; Shokr, Bassel; Assi, Ali; Hallal, Jaafar; Khoury, Paul
Highlights: A study of the effect of dirt accumulation on the productivity of PV panels is done. A robot is designed and manufactured to meet the constraints of the power station. An increase of 32.27% in the power generation was concluded. This paper gave an insight of the dust effects on the power generation in Lebanon. Abstract: In the last two decades, solar energy sources have gained a remarkable place among others and have proven that it is possible to utilize green energy to satisfy a part of the global demands of electrical power. In Lebanon, solar Photovoltaic (PV) systems are being used progressively. However, soiling and dust accumulation, on the surface of these panels, minimizes their efficiency. As a first of its kind in Lebanon, this paper presents the results from a study conducted on the effectiveness of wet cleaning using a robot. This study is carried out on a part of a 1 MWp solar power plant station in Zahrani, a coastal region in Lebanon. The robot was designed, manufactured, implemented, and tested to clean the abovementioned station. The panels were cleaned in a period starting from June 15th to September 30th, 2018. The generated power was collected on a daily basis and compared to the generated power over the same period of 2017 without cleaning. The results showed that the cleaning procedure was able to effectively minimize the effect of dust on the solar panel's power output. Thus, an increase average of 32.27% in the power generation is obtained.